C1QBP Regulates YBX1 to Suppress the Androgen Receptor (AR)-Enhanced RCC Cell Invasion() - Yue, Dan (Neoplasia, 2017)
Early studies suggested that the androgen receptor (AR) might play important roles to promote the renal cell carcinoma (RCC) progression; however, the detailed mechanisms remain unclear. Here we demonstrated the higher YBX1 expression with lower C1QBP expression in human RCC clinical tissues, and the intensity of C1QBP was negatively correlated with the YBX1 nuclear expression. Mechanism dissection found C1QBP could interact with YBX1 to suppress the YBX1 activation via altering the YBX1 phosphorylation and nuclear translocation in RCC cells. The consequences of such suppression of YBX1 might then result in suppressing the RCC cell migration and invasion that involved altering the AR-modulated MMP9 signals. Interruption of this newly identified C1QBP → YBX1 → AR → MMP9-suppressed RCC cell invasion pathway via targeting YBX1 or AR partially reversed the RCC cell invasion. Importantly, results from in vivo mouse model with orthotopic implantation of RCC OSRC2 cells into the left renal capsule also confirmed in vitro cell line studies showing targeting YBX1 could suppress RCC cell invasion via regulation of AR/MMP9 signals. Collectively, these data suggest that C1QBP could regulate YBX1 to suppress the AR-enhanced RCC cell invasion. Targeting this newly identified C1QBP/YBX1/AR/MMP9 signal pathway may provide a new potential therapy to better suppress RCC metastasis.